Determinants of driver response to variable message sign information in Athens. Issue 4 (1st May 2015) - Spyropoulou, Ioanna; Antoniou, Constantinos
Abstract : Variable message signs – which comprise a type of advanced traveller information systems – can affect driver behaviour, especially considering route choice. Hence, their operation is integrated in traffic management strategies for the mitigation of traffic congestion. This research explores the factors determining driver response to variable message signs (VMSs) in the city of Athens. A stated preference questionnaire survey is undertaken and discrete choice analysis is performed towards this aim. More specifically, a random‐effect ordered probit model is estimated that provides insight on the contributory factors that influence driver propensity to divert, when provided with information on incident occurrence via VMSs. Message characteristics, that is, incident type, impact and suggestion for an alternative route, trip characteristics, such as vehicle type, as well as, driver characteristics, such as driver age and income, have been found to affect driver behaviour. Furthermore, appropriate models are also estimated for subsets of the driving population (considering gender and age) and specific similarities and differences between the population behaviours are identified.